Comparison of noncontrast, dynamic, and hepatobiliary phase abbreviated MRI protocols for detection of hepatic malignancies - Lee, Jeong Hyun; Kim, Young Kon; Min, Ji Hye; Cha, Dongik; Hwang, Jeong Ah; Ahn, Soohyun (Clinical Imaging, 2023)
Background: Abbreviated MRI for surveillance in patients at risk for hepatocellular carcinoma (HCC) has recently gained interest. Purpose: To compare the performance among the three types of abbreviated MRI protocols for the detection of hepatic malignancies in patients at risk for HCC. Material and methods: This retrospective review using data from a prospective-registry study included 221 patients with one or more hepatic nodules detected during surveillance for chronic liver disease. Patients underwent MRI with extracellular contrast agents (ECA-MRI) and MRI with hepatobiliary agents (HBA-MRI) before surgery. Sequences from each MRI were extracted to create three simulated abbreviated MRI (aMRI) sets: noncontrast aMRI (NC-aMRI), dynamic aMRI (Dyn-aMRI), and hepatobiliary phase aMRI (HBP-aMRI). Two readers evaluated each set and reported the probability of malignancy and possibility of non-HCC malignancy per lesion. Using the pathology report as reference, the diagnostic performance of each aMRI was compared. Results: This study included 289 observations (219 HCCs, 22 non-HCC malignancies, and 48 benign lesions). Defining category definite malignancy as test positive, the performance of each aMRI was as follows: sensitivity, 94.6%, 88.8%, and 92.5%; and specificity, 83.3%, 91.7%, and 85.4% for HBP-aMRI, Dyn-aMRI, and NC-aMRI, respectively. Pairwise comparison revealed higher sensitivity of HBP-aMRI than both Dyn-aMRI (P = 0.003) and NC-aMRI (P = 0.025), and higher specificity of Dyn-aMRI than HBP-aMRI (P = 0.046). Conclusion: HBP-aMRI showed better sensitivity than Dyn-aMRI or NC-aMRI, whereas the sensitivity of NC-aMRI was comparable to Dyn-aMRI in the detection of malignancy in high-risk patients. Dyn-aMRI showed better specificity than HBP-aMRI.
Keywords: Chronic liver disease; Cirrhosis; Contrast agent; Extracellular; HBV; Hepatobiliary; Hepatocellular carcinoma; Performance; Prospectives; Surveillance; Carcinoma, Hepatocellular; Contrast Media; Gadolinium DTPA; Humans; Liver Neoplasms; Magnetic Resonance Imaging; Prospective Studies; Retrospective Studies; Sensitivity and Specificity; Cirrhosis; HBV; HCC; Screening; Surveillance